2020
DOI: 10.14715/cmb/2020.66.6.8
|View full text |Cite
|
Sign up to set email alerts
|

Significance changes in the levels of myocardial enzyme in the child patients with Mycoplasma Pneumoniae Pneumonia

Abstract: Mycoplasma is a gram-negative with thin wall bacterium that in humans, Mycoplasma pneumoniae causes pneumonia. This experiment was designed to explore the changes of myocardial enzymes in the mycoplasma pneumoniae pneumonia (MPP) child patients, and analyze the clinical value of these changes, in combination with the relevant indicators, symptoms and signs, in the evaluation of the pneumonia mycoplasma infection. For this aim, a total of 120 child patients with MPP in the acute phase,120 child patients with MP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…In recent years, MP showed a yearly upward trend in the detection of pneumonia, this study reported the frequency of MP in pediatric patients diagnosed with CAP was identified in 21.0%, which was similar to several reports [44,45], however, other studies report lower frequencies [46,47]. 33.0% of HBoV-positive patients co-infected with MP in our research, compared with the other group who did not co-infected with MP in HBoV infection children, lower level of AST was found, but a study showed that Mycoplasma pneumoniae pneumonia patients in the acute phase had higher levels of AST than those of the patients in the recovery patients and healthy children [48]. It was also reported that AST level of patients with Chlamydia pneumonia was higher than that of Mycoplasma pneumonia [49].…”
Section: Variablesupporting
confidence: 90%
“…In recent years, MP showed a yearly upward trend in the detection of pneumonia, this study reported the frequency of MP in pediatric patients diagnosed with CAP was identified in 21.0%, which was similar to several reports [44,45], however, other studies report lower frequencies [46,47]. 33.0% of HBoV-positive patients co-infected with MP in our research, compared with the other group who did not co-infected with MP in HBoV infection children, lower level of AST was found, but a study showed that Mycoplasma pneumoniae pneumonia patients in the acute phase had higher levels of AST than those of the patients in the recovery patients and healthy children [48]. It was also reported that AST level of patients with Chlamydia pneumonia was higher than that of Mycoplasma pneumonia [49].…”
Section: Variablesupporting
confidence: 90%
“…In addition, the results are easily affected by the status of pediatric patients with previous infection. Reportedly, some disorder occurs in humoral immunity and cellular immunity in children infected with MP, which is directly proportional to the infection status, indicating the occurrence of MP may be associated with the immune mechanism 4 …”
Section: Introductionmentioning
confidence: 99%
“…When we analysed the correlation between the miR-10a-3p expression level and laboratory inflammatory indicators, we found a positive correlation between miR-10a-3p expression level and WBC, ESR, and CRP. Indicators such as WBC, ESR, and CRP play a role in the evaluation of pneumonia and the determination of treatment efficacy and are associated with progression of pneumonia in a certain sense (9,17). These results suggest that upregulation of miR-10a-3p expression in paediatric MPP might participate in disease development and progression.…”
Section: Changes In Expression Levels Of Nf-κb Signalling Pathwayrelated Proteins and Crp In Thp-1 Cells After Transfectionmentioning
confidence: 88%
“…They have high specificity in the regulation of their target genes. In addition, due to the time and tissue specificity of their regulation, miRNAs can perform very precise regulation of many biological processes (9). The expression levels of miRNAs are altered in various diseases, including autoimmune diseases, cancer, and infectious diseases, and they are associated with the pathogenesis of the diseases (2,8,10).…”
Section: Introductionmentioning
confidence: 99%